Natural Killer Cells from Patients with Recombinase-Activating Gene and Non-Homologous End Joining Gene Defects Comprise a Higher Frequency of CD56bright NKG2A+++ Cells, and Yet Display Increased Degranulation and Higher Perforin Content - Dobbs, Kerry; Tabellini, Giovanna; Calzoni, Enrica; Patrizi, Ornella; Martinez, Paula; Giliani, Silvia Clara; Moratto, Daniele; Al-Herz, Waleed; Cancrini, Caterina; Cowan, Morton; Bleesing, Jacob; Booth, Claire; et al. (Frontiers in Immunology, 2017)
Mutations of the recombinase Activating Genes 1 and 2 (RAG1, RAG2) in humans are associated with a broad range of phenotypes. For patients with severe clinical presentation, hematopoietic stem cell transplantation (HSCT) represents the only curative treatment, however high rates of graft failure and incomplete immune reconstitution have been observed, especially after unconditioned haploidentical transplantation. Studies in mice have shown that Rag-/- NK cells have a mature phenotype, reduced fitness and increased cytotoxicity. We aimed to analyze NK cell phenotype and function in patients with mutations in RAG and in non-homologous end joining (NHEJ) genes. Here we provide evidence that NK cells from these patients have an immature phenotype, with significant expansion of CD56bright CD16-/int CD57- cells, yet increased degranulation and high perforin content. Correlation was observed between in vitro recombinase activity of the mutant proteins, NK cell abnormalities, and in vivo clinical phenotype. Addition of serotherapy in the conditioning regimen, with the aim of depleting the autologous NK cell compartment, may be important to facilitate engraftment and immune reconstitution in patients with RAG and NHEJ defects treated by HSCT.